COVID-19 Preventative Measures: Do-It-Yourself Cloth Face Coverings (Mandarin Chinese) - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS, 2020)
This is the Mandarin Chinese translation of FSHN20-31/FS373: COVID-19 Preventative Measures: Do-It-Yourself Cloth Face Coverings. It provides guidance for making and caring for facemasks. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020.